A robótica educacional e o pensamento computacional no ensino médio - Evaristo, Ingrid Santella (2024)
This study is linked to the Postgraduate Program in Education at Universidade Nove de Julho (PPGE – UNINOVE), in particular to the Educational Policy Research Line (LIPED). The object of study is the analysis of educational robotics and computational thinking in high school. Starting from this object of study, some concerns emerged that motivated and directed the development of this research: what national public policies indicate in relation to the insertion of digital information and communication technologies in high school and what specificities are pointed out for the use of educational robotics and of computational thinking in the school context? How have educational robotics and computational thinking been articulated, aiming for their inclusion in high school? What resources and support materials can be used? What is the perception of teachers and students regarding the potential, difficulties and challenges of implementing pedagogical practices that combine robotics and computational thinking in high school? With the questions presented, the general objective was to analyze the feasibility of applying educational robotics and computational thinking in Basic Education, especially in High School. As specific objectives of the research we list: (1) identify, through the analysis of public educational policies, the insertion of digital information and communication technologies in Basic Education, especially educational robotics and computational thinking in High School; (2) Understand the possibilities of new curricular components, such as technology and innovation, designed and developed for the integration of educational robotics and computational thinking in high school; and (3) Verify the perception of teachers and students regarding the potential, skills and abilities developed, based on pedagogical practices that articulate educational robotics and computational thinking. Based on the objectives presented, the research was then developed according to a qualitative approach, developing through a case study. The instruments adopted were document analysis, questionnaires and semi-structured interviews. The research universe was defined as the project: Robotics, Computational Thinking and digital technologies in Basic Education: enhancing learning and skills in processes of resignification of science teaching developed from November 2019 to October 2022, with funding from the National Council for Scientific and Technological Development (CNPq), Ministry of Science, Technology, Innovations and Communications (MCTIC), based on the Universal Call MCTIC/CNPq – Notice nº 05/2019 – Science at School Program – Science Teaching in Basic Education and support from Nove de Julho University (Uninove). To this end, the analysis of educational robotics and computational thinking in high school was adopted as a focus in this investigation. The research is based on the following authors: Antônio Joaquim Severino, José Armando Valente, Jeannette Wing, Laurence Bardin, Marc Prensky, Seymour Papert, among others. The main results achieved with this study provided the understanding that the pedagogical practices that articulated educational robotics and computational thinking expanded the possibilities for building new knowledge, in a collaborative, meaningful and contextualized way. Furthermore, the results highlighted the challenges of the school curriculum, teacher training, interdisciplinarity and student engagement considered essential in high school.